The intersection of disability and race/ethnicity on victimization risk - Daigle, Leah E. (Journal of ethnicity in criminal justice, 2023)
Although research has demonstrated a link between disability and victimization risk, less is known about how disability and race/ethnicity intersect to impact victimization risk. Using the routine activities/lifestyle perspective as a guide, we explore the relationship between having six disability types and three victimization types (violent, sexual, IPV) across racial/ethnic groups. In doing so, data from the ACHA-NCHA II Spring 2016–2019 surveys are used. Multivariate models examine if having a specific disability increases victimization risk for different racial/ethnic groups. Our findings suggest that disability does not interact with race/ethnicity in elevating risk for victimization in any systematic way, but some differences emerge. These findings support the use of culturally sensitive prevention programs to target at-risk groups.